2012
DOI: 10.1080/02772248.2012.730199
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of human liver carcinoma (HepG2) cells exposed to the marine toxin okadaic acid

Abstract: The marine toxin, okadaic acid (OA) is produced by dinoflagellates of the genera Prorocentrum and Dinophysis and is the causative agent of the syndrome known as diarrheic shellfish poisoning (DSP). In addition, OA acts as both a tumor promoter, attributed to OA-induced inhibition of protein phosphatases as well as an inducer of apoptosis. To better understand the potentially divergent toxicological profile of OA, the concentration dependent cytotoxicity and alterations in gene expression on the human liver tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Thus, Ishida et al [ 66 ] found different cell cycle arrest in myeloid leukemic cells, either at G 1 /S phase or at G 2 /M phase, depending on the OA dose. Recently, Fieber et al [ 75 ] also observed that OA stimulates genes involved in the cell cycle progress at low concentrations whereas it promotes apoptosis at high concentrations. These results support the previous ones in which OA was found to induce mitotic arrest, followed by apoptosis in a synchronized manner [ 67 ].…”
Section: Oa Beyond Its Role As Dsp Inductormentioning
confidence: 99%
“…Thus, Ishida et al [ 66 ] found different cell cycle arrest in myeloid leukemic cells, either at G 1 /S phase or at G 2 /M phase, depending on the OA dose. Recently, Fieber et al [ 75 ] also observed that OA stimulates genes involved in the cell cycle progress at low concentrations whereas it promotes apoptosis at high concentrations. These results support the previous ones in which OA was found to induce mitotic arrest, followed by apoptosis in a synchronized manner [ 67 ].…”
Section: Oa Beyond Its Role As Dsp Inductormentioning
confidence: 99%